2013
DOI: 10.1103/physrevlett.110.177201
|View full text |Cite
|
Sign up to set email alerts
|

Topology and Origin of Effective Spin Meron Pairs in Ferromagnetic Multilayer Elements

Abstract: We report on pairs of converging-diverging spin vortices in Co/Rh/NiFe trilayer disks. The lateral magnetization distribution of these effective spin merons is directly imaged by means of element-selective x-ray microscopy. By this method, both the divergence and circulation states of the individual layers are identified to be antisymmetric. Reversal measurements on corresponding continuous films reveal that biquadratic interlayer exchange coupling is the cause for the effective meron pair formation. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…the orientation of the magnetization vector covers half of the unit sphere. A variety of merons has been identified in magnetic systems, such as in-plane magnetic vortices [23], or at endpoints of helical or PMA stripes [16,[24][25][26][27][28][29]. In this second case, the magnetic configuration at the stripe endpoint in a 2D magnetic film consists of an in-plane half vortex plus an out-of-plane polarity change (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…the orientation of the magnetization vector covers half of the unit sphere. A variety of merons has been identified in magnetic systems, such as in-plane magnetic vortices [23], or at endpoints of helical or PMA stripes [16,[24][25][26][27][28][29]. In this second case, the magnetic configuration at the stripe endpoint in a 2D magnetic film consists of an in-plane half vortex plus an out-of-plane polarity change (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…First evidence on the existence of hedgehog meron pairs comes from a study on a magnetic trilayer disk where two ferromagnetic (FM) disks are antiferromagnetically (AFM) coupled through a spacer layer [15]. Direct proof of the hedgehog-like meron pair structure, however, was provided only by using elementresolved magnetic imaging [16]. It was shown that the spin flux closure leads to an antisymmetric relation in the divergence and circulation of the two merons.…”
Section: Introductionmentioning
confidence: 99%
“…We introduce an additional dimension to the collective gyrations of vortices known from spin-torque oscillators [22]. Stacking the vortices allows for a strongly increased packing density and has thus stimulated recent studies [23][24][25][26][27][28][29][30]. While for two-dimensional arrangements the minimization of the stray fields at the side surfaces creates the vortices and mediates their interaction, we observe a second coupling mechanism for three-dimensional stacks that has been investigated theoretically [26,31,32].…”
Section: Introductionmentioning
confidence: 91%